Numerical Analytic Solution of SIR Model of Dengue Fever Disease in South Sulawesi using Homotopy Perturbation Method and Variational Iteration Method - Yulita Molliq Rangkuti; Syafruddin Side; Mohd Salmi Md Noorani (Institute for Research and Community Services (LPPM) ITB, 2014)
In this research, the susceptible